Issues in selecting profitability indicators for the evaluation of corporate financial performance - Savickas, Vilius (Buhalterinės apskaitos teorija ir praktika, 2020)
The article analyses the selection of profitability indicators for the evaluation of corporate financial performance. Both theory and practice, address a variety of profitability indicators, therefore, it is essential to understand the possibilities of using the information they provide, as well as to be able to identify potential reasons of indicator value deviations, and to assess the conditions causing the analysis performed based on these indicators to provide incomplete or unreliable information. The aim of the study is to analyse the main profitability indicators, their potential disadvantages, and possible issues in the analysis and interpretation of these indicators. Methods of logical and comparative analysis of the scientific literature, synthesis and generalisation, statistical data analysis and interpretation were used in this article. The results of the analysis show that there is no universal profitability indicator, that would cover all areas of company performance, because profitability indicators’ reliability, as well as objectivity of comparison to other entities, are influenced by national accounting standards, different prime cost calculation methods, long-term assets depreciation methods, reserve assessment, and other methods.